A NEW SPECIES OF GENTIANA (GENTIANACEAE) FROM THE SIKKIM HIMALAYA. (7th November 2014) - Maity, D.
<x content-type="archive" xml:space="preserve">Abstract</x> Gentiana springateana D.Maity sp. nov. (Gentianaceae) is described from the Sikkim Himalaya and placed in G. section Phyllocalyx (Kusn.) T.N.Ho. This new taxon is described and illustrated, and compared morphologically with two related taxa, Gentiana phyllocalyx C.B.Clarke and G. urnula Harry Sm.